2015
DOI: 10.1186/s12917-015-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inulin affects the intestinal microbiota in sows and their suckling piglets

Abstract: Background: Several studies have focused on the effects of dietary inulin on the intestinal microbiota of weaned piglets. In the present study, inulin was added to a diet for gestating and lactating sows, expecting not only effects on the faecal microbiota of sows, but also on the bacterial cell numbers in the gastrointestinal tract of their piglets during the suckling period. Sows were fed a diet without (n = 11) or with (n = 10) 3% inulin, and selected bacterial groups were determined in their faeces ante an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 26 publications
4
39
1
Order By: Relevance
“…Nevertheless, Lactobacillus CFU is higher at 24 hr of lactation ( p = .0340). These findings match with those of Paßlack, Vahjen, and Zentek (). The results obtained correspond to the normal colonization of the microbiota which is an important aspect as any alteration in the chronological development of the implantation of the microbiota will impact on the productive future of the animal (Bauer, Williams, Smidt, Verstegen, & Mosenthin, ; Buffie et al., ; Round & Mazmanian, ).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, Lactobacillus CFU is higher at 24 hr of lactation ( p = .0340). These findings match with those of Paßlack, Vahjen, and Zentek (). The results obtained correspond to the normal colonization of the microbiota which is an important aspect as any alteration in the chronological development of the implantation of the microbiota will impact on the productive future of the animal (Bauer, Williams, Smidt, Verstegen, & Mosenthin, ; Buffie et al., ; Round & Mazmanian, ).…”
Section: Discussionsupporting
confidence: 91%
“…No statistically signifi cant differences were found in other investigated faecal microorganisms (Table 4), except for the increase in the numbers of Enterococcus. Paßlack et al [2015] also showed that dietary inulin supplementation (3%) increased the numbers of enterococci, but it is contrary to other studies [Kleesen et al, 2007;Waitzberg et al, 2012].…”
Section: Results Of Medical Examinationcontrasting
confidence: 60%
“…But the results are controversial because of the differences in animal and human study models. Despite the variety of the data, it seems that inulin is likely to have a benefi cial impact on health status, especially in cases of infl ammation, infection and non-infectious diseases, during antibiotic and other drug consumption, constipation and other conditions when human intestinal microfl ora might be changed [Kleessen et al, 2007;Waitzberg et al, 2012;Paßlack et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially relevant in swine production with each farm microbial environment being different and possibly impacting animal health status and the productive outcome. It has been shown that maternal diet or antibiotic treatment may induce a long lasting impact on the establishment of gut microbiota, gut biology and growth performances of offspring pigs [46]. However, none of these studies have associated the early-life fecal microbiota diversity and composition to the further suceptibility of post-weaning diarrhea in pigs.…”
Section: Introductionmentioning
confidence: 99%